2003
DOI: 10.1104/pp.103.022749
|View full text |Cite
|
Sign up to set email alerts
|

Regulated Phosphorylation of 40S Ribosomal Protein S6 in Root Tips of Maize

Abstract: Ribosomal protein S6 (RPS6) is located in the mRNA binding site of the 40S subunit of cytosolic ribosomes. Two maize (Zea mays) rps6 genes were identified that encode polypeptides (30 kD, 11.4 pI) with strong primary amino acid sequence and predicted secondary structure similarity to RPS6 of other eukaryotes. Maize RPS6 was analyzed by the use of two-dimensional gel electrophoresis systems, in vivo labeling with [ 32 P]P i and immunological detection. Nine RPS6 isoforms were resolved in a two-dimensional basic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
124
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(134 citation statements)
references
References 54 publications
(69 reference statements)
7
124
0
3
Order By: Relevance
“…Phosphorylation of ribosomal protein S6 and p70 S6 kinase has also been reported in maize (Williams et al, 2003;de la Cruz et al, 2004). For ribosomal protein S6, phosphorylated isoforms in Ser-238 and Ser-241 have been described (Williams et al, 2003), while for p70 S6 kinase, residue Thr-389 was found to be phosphorylated in correlation with its activation (de la Cruz et al, 2004).…”
Section: Phosphorylation Of Ribosomal Protein S6 and Its Protein Kinamentioning
confidence: 78%
See 3 more Smart Citations
“…Phosphorylation of ribosomal protein S6 and p70 S6 kinase has also been reported in maize (Williams et al, 2003;de la Cruz et al, 2004). For ribosomal protein S6, phosphorylated isoforms in Ser-238 and Ser-241 have been described (Williams et al, 2003), while for p70 S6 kinase, residue Thr-389 was found to be phosphorylated in correlation with its activation (de la Cruz et al, 2004).…”
Section: Phosphorylation Of Ribosomal Protein S6 and Its Protein Kinamentioning
confidence: 78%
“…Phosphorylation of S6 was described previously in plant ribosomes. In response to several stress treatments, hyperphosphorylated isoforms of S6 accumulate in maize root tips (Williams et al, 2003). Of particular interest are the Ser-238 and Ser-241 residues, because these are differentially phosphorylated after specific environmental changes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A carboxy-terminal region of RPS6 has been shown to be phosphorylated by S6K1 in animal cells (Krieg et al, 1988;Radimerski et al, 2000) as well as in plant (Williams et al, 2003). In addition, the GFP-S6K1 was shown to be able to phosphorylate a carboxy-terminal region of Arabidopsis RPS6 (a.a. 150-249; AtRPS6-CT) (Mahfouz et al, 2006).…”
Section: Resultsmentioning
confidence: 99%